Differential impacts of regenerative agriculture practices on soil organic carbon: a meta-analysis of studies from India - Patil, Mukund; Perumal, Cuba; Choudhari, Pushpajeet L.; Pasumarthi, Rajesh; Sawargaonkar, Gajanan; Singh, Ramesh (Springer Nature, 2025)
Regenerative agriculture (RA) is heralded as a transformative solution to combat climate change, enhance biodiversity, and improve soil health. However, its effectiveness across diverse agro-climatic contexts remains underexplored. This meta-analysis synthesizes results from 147 peer-reviewed studies across India’s major agro-ecological and agro-climatic regions. Using a random-effects model, we estimate the soil organic carbon (SOC) change attributable to a suite of RA practices, including organic amendments (farmyard manure, green manure, compost, and biochar), conservation tillage, crop residue retention, and fertilizer management. Biochar application resulted in the highest SOC gain, followed by farmyard manure, green manure, compost, and fertilizer management. Conservation tillage and crop residue retention demonstrated moderate, yet consistent, carbon benefits across time scales. The SOC gains were most significant over durations exceeding five years and varied across agro-ecological regions, with semi-arid and sub-humid regions showing particularly strong responses. The findings affirm that RA practices effectively sequester carbon, particularly when applied over longer durations and in regionally adapted combinations.